Dirichlet Averages of Generalized Multi-index Mittag-Leffler Functions - Saxena, R.K.; Pogany, T.K.; Ram, J.; Daiya, J. (Armenian Journal of Mathematics, 2011)
The object of this article is to investigate the Dirichlet averages of the generalized multi--index Mittag--Leffler functions introduced by Saxena and Nishimoto \cite{23, 24}. Representations of such relations are obtained in terms of Riemann--Liouville integrals and hypergeometric functions of several variables. Some interesting special cases of the established results associated with generalized Mittag--Leffler functions due to Srivastava and Tomovski \cite{28} and multi--index Mittag--Leffler functions due to Kiryakova \cite{13} are deduced. Certain results given earlier by Kilbas {\em et al.} \cite{9} also follow as special cases of our findings.